1999
DOI: 10.1161/01.hyp.34.3.375
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Systolic Hypertension

Abstract: Abstract-Increased arterial stiffness results in increased characteristic impedance of the aorta and increased pulse wave velocity, which increases systolic and pulse pressures. An association between increased pulse pressure and adverse cardiovascular events has been found in normotensive and hypertensive patient populations. Increased pulse pressure has also been associated with thickening of the carotid intima and media. However, the relationship between pulse pressure and stroke has not previously been eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
118
2
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(132 citation statements)
references
References 57 publications
8
118
2
4
Order By: Relevance
“…The association between arterial stiffness measured by carotid‐femoral PWV index and stroke, which was also adjusted for MAP, has, however, been described previously 31. Also the associations of PP with stroke are inconsistent with earlier work in older people with isolated systolic hypertension, where they found an 11% increased risk per 10 mm Hg higher PP, but also showed that MAP increased risk of stroke 38. However, a later study in uncontrolled hypertensive subjects found, similar to this study, that the relationship between PP and stroke was dependent on MAP,39 indicating that MAP may be a confounder in the association between PP and stroke.…”
Section: Discussionmentioning
confidence: 69%
“…The association between arterial stiffness measured by carotid‐femoral PWV index and stroke, which was also adjusted for MAP, has, however, been described previously 31. Also the associations of PP with stroke are inconsistent with earlier work in older people with isolated systolic hypertension, where they found an 11% increased risk per 10 mm Hg higher PP, but also showed that MAP increased risk of stroke 38. However, a later study in uncontrolled hypertensive subjects found, similar to this study, that the relationship between PP and stroke was dependent on MAP,39 indicating that MAP may be a confounder in the association between PP and stroke.…”
Section: Discussionmentioning
confidence: 69%
“…H emodynamics research has shifted away from a steadyflow approach toward a pulsatile flow approach, because the former was less predictive in relation to cardiovascular morbidity and mortality. [1][2][3][4][5] The growing importance of pulsatile pressure indices (systolic blood pressure [SBP] and pulse pressure) paralleled the notion that not only increases in systemic vascular resistance (SVR) but also increases in arterial stiffness are important in the pathophysiology of hypertension. 6,7 This interest in the arterial cushioning function of pulsatile flow has given us a myriad of arterial stiffness indices generated by a wide array of methodologically varied noninvasive measurement techniques.…”
mentioning
confidence: 99%
“…[23][24][25][26] The randomized multicenter clinical trial Systolic Hypertension in the Elderly Program found that in patients with ISH a decrease of the DBP and concomitant increase in PP increased the risk for stroke, coronary heart disease, and cardiovascular disease. 26 This study also showed that the occurrence of both Probabilities were determined from generalized estimation equation analysis for male gender with age 55 years.…”
Section: Discussionmentioning
confidence: 99%